ISOLATION AND IDENTIFICATION OF SECONDARY METABOLITE FROM ETHYL ACETATE EXTRACT OF PETROSIA SP. AND ITS ANTIOXIDANT ACTIVITY - Muhammad Hajrul Malaka; Hartina Hartina; Adryan Fristiohady; Baru Sadarun; I Sahidin (Universitas Muhammadiyah Magelang, 2021)
Sponges are marine organism that contain various chemical compound with potential pharmacological activities. This study aims to isolate and identify secondary metabolites from ethyl acetate extract of Petrosia sp. and its antioxidant properties. Extraction was performed by maceration using ethyl acetate. Isolation methods were carried out using Thin Layer Chromatography (TLC), Vacuum Liquid Chromatography (VLC), and Radial Chromatography (RC) technique. Isolated compound was identified by 1D-NMR (1H and 13C NMR) and 2D-NMR (HMQC and HMBC). Antioxidant assay was determined by its activity against ABTS radical. Isolated compound identified as an alkaloid namely 6-hydroxy-1,3,7-trimethyl-3,5-dihydro-1-Himidazo [4,5-c] piridine -2,4-dione. Antioxidant activity test showed Petrosia sp. extract was active as antioxidant with IC50 values 27.20 μg/mL against DPPH and 27.53 μg/mL against ABTS, whereas isolated compound was inactive against DPPH and ABTS with IC50 values 242.64 μg/mL. Meanwhile, Vitamin C was very active against DPPH and ABTS with IC50 21.51 μg/mL and 22.21 μg/mL, respectively.